'N TIPIESE S.A. LUGMAGOFFISIERSPERSOONLIKHEID? - Smuts, B.W. (Scientia Militaria - South African Journal of Military Studies, 2012)
Selection and training are integral functions of modern military activity. Although a typical air force officer personality does not appear to exist, these tests do serve as a pointer towards the question of career satisfaction.